Variation in the fat mass and obesity‐related (FTO) genotype is not associated with body fatness in infants, but possibly with their length. Issue 5 (21st May 2014) - Henriksson, P.; Löf, M.; Söderkvist, P.; Forsum, E.
Summary Background Data relating variation at the fat mass and obesity‐related (FTO) locus (rs9939609) to fat mass in infancy are inconclusive. Objective To study relationships between FTO genotype and infant size (at 1 and 12 weeks and at 1 year of age) and body composition (at 1 and 12 weeks). Methods Body composition was assessed using air displacement plethysmography in 207 infants. FTO was genotyped using the TaqMan assay. Results The number of risk alleles was related to length at 1 and 12 weeks (P = 0.007–0.033) but not to fat mass. The relationship to length was stronger in boys than in girls. Conclusions Our results suggest that the FTO genotype is not related during infancy to fat mass but is related to length in boys but not in girls.